Factors related to the incidence of Breast Cancer in Outpatient Care at Haji Medan Hospital in 2025 - Fasha Permata Chairani; Rahayu Lubis (Jurnal Geografi, Lingkungan dan Kesehatan, 2026)
Breast cancer remains a major cause of cancer-related mortality among women worldwide. In 2024, RSU Haji Medan recorded 1,665 outpatient cases. This study aimed to identify factors associated with breast cancer incidence in outpatients at RSU Haji Medan in 2025. A quantitative cross-sectional study was conducted among 114 purposively selected respondents. Data were collected using structured interviews and analyzed through univariate and bivariate methods, presenting odds ratios (OR) with 95% confidence intervals (CI). Significant factors associated with breast cancer incidence included age (OR = 2.15, 95% CI: 1.15–4.03, p = 0.016), family history (OR = 2.85, 95% CI: 1.32–6.13, p = 0.007), early menarche <12 years (OR = 1.98, 95% CI: 1.09–3.62, p = 0.024), breastfeeding <6 months (OR = 2.65, 95% CI: 1.41–4.98, p = 0.002), and hormonal contraceptive use (OR = 3.21, 95% CI: 1.65–6.23, p = 0.001). Age at first birth showed no significant association (p = 0.651). Breast cancer incidence among outpatients is strongly associated with age, family history, early menarche, short breastfeeding duration, and hormonal contraceptive use. Targeted prevention strategies and early screening programs are urgently needed for high-risk groups.